Medical Doctor and Dental Students’ Views on Enrolling in Medical Doctor and Dentistry Majors for Their Higher Education Degrees in Cambodia: A Survey Study - Sorn, Virak; Saut, Sopheakpanha (Journal of Mathematics Instruction, Social Research and Opinion, 2024)
The purpose of this study is to explore the views of students taking medical doctor (MD) and dentistry (DD) majors on why they were learning what they were learning and to contextualize how these views would impact their studies. A mixed-methods approach was used in this study. An anonymous Google form was utilized to get quantitative data, while FGDs were used to gather qualitative data. The qualitative data were thematically evaluated, and the quantitative data were analyzed using SPSS. The findings demonstrated the factors that motivated them to enroll in the MD and DD programs and the reasons behind this enrollment. These factors include their interest in future career perspectives, academic performance, life experience, role models, and family direction. However, the results also indicated that university profiles impacted students’ decisions about choosing a health science university for these MD and DD majors, which require a long journey to graduate.